Phenology of Acacia nilotica and Eucalyptus microtheca at Wad Medani (Sudan) - Waheed Khan, M. A. (Indian Forester, 1970)
In the Eastern Sudan, by far the most important forest tree species of economic value are Acacia nilotica and Eucalyptus microtheca. The former species occurs naturally along the Blue Nile river and its affluents. The latter is extensively raised in irrigated plantations. Understanding the phenology of these two species is of immense importance for manipulation of such operations as prediction of seed crops, seed collection, establishment of seed production areas, tree improvement programme, application of fertilizers, spraying as a protective measure, etc. Phenological studies were made on one single-stemmed tree of A. nilotica and four trees of E. microtheca, ranging in stem numbers from 1 to 4. The period of observations was spread from 25.2.1963 to 10.7.1967, i.e., over 49Â½ months and involving 97 observations spaced at fortnightly intervals. Leafing behaviour of both A. nilotica and E. microthera is almost identical. They never become completely leafless. In both cases leafing starts in July and attains a peak during August to April. Decline in leafing occurs during May and June. In E. microtheca, there is a definite correlation of decreasing litter production with increasing leafing phenological value. The annual occurrence of flowering, fruiting and seeding differs signficantly between the two species. In A. nilotica, there is only one annual rhythm of these processes; whereas in E. microtheca there are two, viz., first rhythm of winter and second rhythm of summer. The latter recurs with unfailing regularity year after year. The first rhythm of winter, however, is not only milder in intensity but also occurs periodical1y and not annually. Sometimes, its flowering phase may be completely arrested and may not proceed to produce fruiting and seeding. Roughly, this first rhythm of winter may occur once or twice each four years. In A. nilotica, the reproductive phase lasts from July to May. Flowering occurs during July to January, with peak during September-October. Fruiting lasts from October to March, with peak during December to February; and seeding spreads from January to May, with peak period during March-April. In comparable summer rhythm of E. microtheca, the reproductive phase lasts from February to July. Flowering occurs from February to June (with peak during March to May), fruiting from April to June (with peak during May), and seeding from May to July (with peak during June). The winter reproductive rhythm of E. microtheca spreads from October to February. Flowering occurs during October to December (with peak during November), fruiting from November to January (with peak during December), and seeding from December to February (with peak during January). The phenological behaviour of A. nilotica is mainly governed by rainfall, temperature and evaporation. Rainfall primarily influences leafing, whereas temperature affects flowering and fruiting. Seeding is controlled by evaporation. In E. microtheca, the phenological behaviour of the variously-stemmed trees is practically the same. Generally speaking, leafing is mainly influenced by the amount and distribution of rainfall. Flowering is affected both by relative humidity and evaporation. In fruiting, temperature also plays a part besides these two climatic elements. Seeding is primarily influenced only by temperature. The occurrence of winter reproductive rhythm is influenced only by the total rainfall and cloud amounts. In this respect, climate during October is all important. Almost the absence of rainfall combined with low occurrence of clouds, induces commencement of flowering. For fruiting and seeding to succeed, it is necessary that not only rainless conditions should persist but the cloud occurrence conditions should also continue. Almost clear skies inhibit these processes.